PENGARUH PERSEPSI SISWA DALAM PENGGUNAAN WHATSAPP SEBAGAI MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR IPA SELAMA DARING - Huda, M. Komarul; Wilson Sitopu, Joni; Junita (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study aimed to determine the influence of students' perceptions of using WhatsApp as a learning medium on their motivation to learn science online at SMP Negeri 10 Pematangsiantar in the 2020/2021 academic year. The population was all 7th-grade students, consisting of 231 students in 7 classes. The sample was selected using proportional random sampling, with 58 students. Data analysis was performed using normality, linearity, homogeneity, and hypothesis testing, including correlation coefficients, t-tests, coefficients of determination, and linear regression. The normality test results obtained a significance value of 0.946 > 0.05, the linearity test results obtained a significance value of 0.805 > 0.05, the homogeneity test results obtained a value of 0.284 > 0.05, the correlation coefficient test results obtained a value of 0.229, indicating a low correlation level between the influence of student perceptions in the use of WhatsApp on science learning motivation. The coefficient of determination test results obtained 0.35 indicating an influence of student perceptions in the use of WhatsApp on science learning motivation with a percentage level of 3.5%. The results of the linear regression test showed a significance value of 0.084 > 0.05, so it can be concluded that variable x influences variable y. Based on the t value, the calculated t value is 81.163 > t table 1 1.67252, so it can be concluded that variable x influences variable y. Based on the data analysis, it can be concluded that the influence of student perceptions in the use of WhatsApp as a learning medium on student learning motivation during online learning has a low influence,namely 3.4%.